Parking availability identification system in urban areas of through image processing Lima - Peru - Meneses Claudio, Brian (2022)
A challenge of the automobile is to find a solution to this problem of vehicle parking, since the number of vehicles grows annually and there is no sophisticated system that allows to reduce waiting times and perform this task more efficiently, becoming an important aspect for the best use of the capacity of the existing parking area, being the main focus the increase in the number of vehicles that affect the undistributed filling of the parking lot generating waiting time and in many cases desertion in supermarkets. In our country it is necessary to increase parking spaces since many people have vehicles and the number of vehicles continues to increase every year, although there are companies dedicated to this area, they do not achieve the comfort of people for various reasons such as vehicle safety and the distance in which the vehicle is. In view of this problem, this article made a system of identification of availability in parking lots in urban areas of Lima - Peru through image processing to facilitate the user's search for a parking area that is free. Through the development of the system, the objective of detecting the free spaces so that users can park their vehicles according to a previous complete evaluation conducted by the system with an efficiency of 98.14% was met.